The Process of Thinking among Junior High School Student in Solving HOTS Question - Bakry Bakry; Md Nor Bin Bakar (Institute of Advanced Engineering and Science, 2015)
Higher order thinking skills (HOTS) is one of the important aspect of teaching and learning mathematics. By using HOTS, student will be able to acquire a deep understand of mathematical concepts and can be applied in real life. Students ability to develop the capacity of the HOTS is closely related with thinking processes while solving mathematics problems. This research focused, at describing the thinking process of students in solving mathematical problem involving HOTS problem. The method used is a qualitative method and case study design, the data collected through mathematics tests and interviews. There are 3 students selected as participant Data analysis techniques are descriptive qualitative, analysis according to the model proposed by Miles and Huberman (1992), namely data reduction, data presentation and conclusion. The result of the study showed that the students thinking process in solving mathematics problem is by using the systematic thinking (1) creating of meaning (2) making of opinion, and 3) making conclution.